ENHANCING CRITICAL THINKING THROUGH LITERARY ANALYSIS - Hikmahyanti, Cita; Neisya, Neisya (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2019)
This study investigated the improvement of students literary analysis by using taxonomy Blooms critical thinking questions. Action research was conducted for this research to the sixth semester students of English literature study program at Universitas Bina Darma. They are 5 male students and 10 female students. The action research was conducted for 12 meetings. On the first cycle, it consisted planning, action, observation and reflection. The assesment for the success criteria scored from a literary analysis rubric with scale poor, fair and good. During this cycle, the students only achieved mostly to poor level of literary analysis in their writing. After doing some revision and evaluation on the second cycle, it also included, replanning, action, observation and the reflection. In this cycle, the result shows most students succeeded to improve their literary analysis to the fair level and 2 students were in good level with some notes. Although, some students perhaps need more time and practises to achieved a good skill.